Chlorido(dimethyl 2, 2′‐bipyridine‐4, 4′‐dicarboxylate‐κ2N, N′)(η5‐pentamethylcyclopentadienyl)rhodium(III) chloride 1‐hydroxypyrrolidine‐2, 5‐dione disolvate. (9th May 2013) - Sivanesan, Dharmalingam; Kim, Hyung Min; Sungho, Yoon
<x xml:space="preserve">Abstract</x> The title complex, [Rh(C10H15)Cl(C14H12N2O4)]Cl·2C4H5NO3, has been synthesized by a substitution reaction of the precursor [bis(2, 5‐dioxopyrrolidin‐1‐yl) 2, 2′‐bipyridine‐4, 4′‐dicarboxylate]chlorido(pentamethylcyclopentadienyl)rhodium(III) chloride with NaOCH3. The RhIII cation is located in an RhC5N2Cl eight‐coordinated environment. In the crystal, 1‐hydroxypyrrolidine‐2, 5‐dione (NHS) solvent molecules form strong hydrogen bonds with the Cl− counter‐anions in the lattice and weak hydrogen bonds with the pentamethylcyclopentadienyl (Cp*) ligands. Hydrogen bonding between the Cp* ligands, the NHS solvent molecules and the Cl− counter‐anions form links in a V‐shaped chain of RhIII complex cations along the c axis. Weak hydrogen bonds between the dimethyl 2, 2′‐bipyridine‐4, 4′‐dicarboxylate ligands and the Cl− counter‐anions connect the components into a supramolecular three‐dimensional network. The synthetic route to the dimethyl 2, 2′‐bipyridine‐4, 4′‐dicarboxylate‐containing rhodium complex from the [bis(2, 5‐dioxopyrrolidin‐1‐yl) 2, 2′‐bipyridine‐4, 4′‐dicarboxylate]rhodium(III) precursor may be applied to link Rh catalysts to the surface of electrodes.